Dose-volume predictors of early esophageal toxicity in non-small cell lung cancer patients treated with accelerated-hyperfractionated radiotherapy - Bütof, Rebecca; Löck, Steffen; Soliman, Maher; Haase, Robert; Perrin, Rosalind; Richter, Christian; Appold, Steffen; Krause, Mechthild; Baumann, Michael (Radiotherapy and oncology, 2020)
Background and purpose - Early radiation-induced esophageal toxicity (RIET) is one of the major side effects in patients with non-small cell lung cancer (NSCLC) and can be a reason for treatment interruptions. As the age of patients with NSCLC and corresponding comorbidities continue to increase, primary radiotherapy alone is a commonly used alternative treatment in these cases. The aim of the present study is to compare dosimetric and clinical parameters from the previously reported CHARTWEL trial for their ability to predict esophagitis and investigate potential differences in the accelerated and conventional fractionation arm. - Material and methods - 146 patients of the Dresden cohort of the randomized phase III CHARTWEL trial were included in this post-hoc analysis. Side effects were prospectively scored weekly during the first 8 weeks from start of radiotherapy. To compare both treatment arms, recorded dose-volume parameters were adjusted for the different fractionation schedules. Logistic regression was performed to predict early RIET for the entire study group as well as for the individual treatment arms. Different dosimetric and clinical parameters were tested. - Results - Patients receiving the accelerated CHARTWEL schedule experienced earlier and more severe esophagitis (e.g. 20.5% vs. 9.6% ≥grade 2 at week 3, respectively). In contrast, the median time period for recovery of grade 1 esophagitis was significantly longer for patients with conventional fractionation compared to the CHARTWEL group (median [range]: 21 [12-49] days vs. 15 [7-84] days, p = 0.028). In univariable logistic regression none of the dose-volume parameters showed a significant correlation with early RIET grade ≥ 2 in the conventional irradiation group. In contrast, for patients receiving CHARTWEL, the physical dose-volumes parameters V40 and V50; and re-scaled values VEQD2,50 and VEQD2,60 were significant predictors of early RIET grade ≥ 2. Dose-volume parameters remained different between CHARTWEL and conventional fractionation even after biological rescaling. - Conclusion - Our results show a more dominant dose-volume effect in the CHARTWEL arm compared to conventional fractionation, especially for higher esophageal doses. These findings support the notion that dose-volume parameters for radiation esophagitis determined in a specific and time dependent setting of field arrangements can not be easily transferred to another setting. In clinical practice esophageal volumes receiving 40 Gy or more should be strictly limited in hyperfractionated-accelerated fraction schemes.
Available online: 22 November 2019
Gesehen am 14.04.2020